POSSIBILITIES OF 3D MACHINING OF MATERIALS BY ABRASIVE WATER JETS - Raška, Jan; Tyč, Martin; Štefek, Adam; Hlaváč, Libor M. (GeoScience Engineering, 2019)
Machining of materials through the classical way, i.e. using conventional tools for turning, drilling, milling, grinding and polishing, has some limits that can be overcome applying an abrasive water jet (AWJ). Therefore, some possibilities of 3D machining by AWJ placed on 6 axes robot have been tested. Programming of traverse speeds and tilting angles of cutting head was based on Hlaváč’s theoretical model. Low-pressure pump has been used for tests. Because of very low pumping pressure, a self-designed and manufactured special mixing chamber was used in the experiments. The article deals with preliminary results and points at the direction of further research. Keywords: abrasive water jet, composite, cutting, trailback, taper http://doi.org/10.35180/gse-2019-0008